Potential roles of suppressor of cytokine signaling in wound healing. (March 2016) - Feng, Yi; Sanders, Andrew J; Morgan, Liam D; Harding, Keith G; Jiang, Wen G
Wound healing is a dynamic process comprising three overlapping, highly orchestrated stages known as inflammation, proliferation and re-epithelialization, and tissue remodeling. This complex process is regulated by numerous cytokines, with dysregulation of cytokine-induced signaling leading to impaired wound healing. Suppressor of cytokine signaling (SOCS) proteins are a family of eight intracellular proteins which may hold the potential to maintain homeostasis during wound healing through their negative feedback inhibition of cytokine signaling. To date, the roles of SOCS proteins in inflammation, autoimmunity and cancer have been comprehensively illustrated; however, only a limited number of studies focused on their role in wound healing. This review demonstrates the possible links between SOCS proteins and wound healing, and also highlights the potential importance of this family in a variety of other aspects of regenerative medicine.